Online self-help programs to reduce psychological distress in mexican college students - Gutiérrez-García, Raúl A.; Amador Licona, Norma; Sánchez Ruiz, Abraham; Fernández Reyes, Pamela Lili (Gaceta Médica de Caracas, 2021)
University students are a key group in society, in terms of human capital and social development. They constitute a risk group in the development of anxiety due to their psychological, social, and academic demands, therefore it is necessary to propose intervention alternatives in this population.